VECTOR CONSTRUCTION FOR SOD GENE OVEREXPRESSION AS AN ATTEMPT TO DEVELOP PHYTOREMEDIATION PLANTS - Yuniati, Ratna; Trisnaningrum, Niken; Salamah, Andi; Handayani, Windri (MATTER: International Journal of Science and Technology, 2015)
We construct a new binary plasmid vector designated pCHISOD, harboring SOD gene. A 564-bp NCO II /Best EIII fragment containing the intact SOD gene and its flanking regions was initially inserted into pCHIE. The purpose of this research was to construct binary plasmid which will introduce the SOD gene into Mel stoma plants in order to create transgenic plants of rphytoremediation of metals. Transgenic plants of M. malabathricum carrying the SOD gene have been developed via Agro bacterium tumefactions-mediated transformation. This method involved the use of leaf explants co-cultivated with disarmed Agro bacterium strain LBA4404, which on the T-DNA region carries SOD genes. The presence of the T-DNA in the regenerated shoots will confirmed by amplification of the transgene using polymerase chain reaction.